2017
DOI: 10.3389/fnmol.2017.00224
|View full text |Cite
|
Sign up to set email alerts
|

Synucleins and Gene Expression: Ramblers in a Crowd or Cops Regulating Traffic?

Abstract: Synuclein family consists of three members, α, β, and γ-synuclein. Due to their involvement in human diseases, they have been thoroughly investigated for the last 30 years. Since the first synuclein identification and description, members of this family are found in all vertebrates. Sequencing of their genes indicates high evolutionary conservation suggesting important function(s) of these proteins. They are small naturally unfolded proteins prone to aggregate, easily change their conformation, and bind to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 92 publications
0
53
0
Order By: Relevance
“…Although the ORs associated with SNCA SNPs were relatively low, previous research has suggested that functional SNCA SNPs can affect SNCA expression through epigenetic modification (Soldner et al, 2016 ), which may allow them to be used as potential therapeutic targets and to contribute to precise treatment strategy design (Carlson, 1990 ). These polymorphisms in SNCA may also possibly affect the risk of PD by damaging the normal function of α-synuclein by affecting synaptic activity through modulating the release of synaptic vesicle (Surguchev and Surguchov, 2017 ). Substitution of amino acids ofα-synuclein changed the gene expression levels including genes functioning in apoptosis, transcription process, membrane proteins, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Although the ORs associated with SNCA SNPs were relatively low, previous research has suggested that functional SNCA SNPs can affect SNCA expression through epigenetic modification (Soldner et al, 2016 ), which may allow them to be used as potential therapeutic targets and to contribute to precise treatment strategy design (Carlson, 1990 ). These polymorphisms in SNCA may also possibly affect the risk of PD by damaging the normal function of α-synuclein by affecting synaptic activity through modulating the release of synaptic vesicle (Surguchev and Surguchov, 2017 ). Substitution of amino acids ofα-synuclein changed the gene expression levels including genes functioning in apoptosis, transcription process, membrane proteins, etc.…”
Section: Discussionmentioning
confidence: 99%
“…These groups have shown that reducing α-synuclein expression leads to reductions in dopaminergic neuron loss alongside fewer motor deficits. Thought, it is crucial to consider that blocking the expression of α-synuclein may interfere with the normal function of this protein (Surguchev and Surguchov, 2017;Burré et al, 2018;Sorrentino et al, 2019;Taguchi et al, 2019).…”
Section: Neurotrophic Factorsmentioning
confidence: 99%
“…α‐Synuclein is localized to neuronal presynaptic terminals and is made up of 140 amino acids and is encoded by the SNCA gene on the long arm of chromosome 4q21.3–q22, which spans 111 kb in length . Whilst still a subject of intense research, α‐synuclein is believed to regulate vesicle trafficking and refilling, endocytosis and neurotransmitter release via interactions with the soluble N‐ethylmaleimide‐sensitive factor attachment protein receptor (SNARE) complex (both t‐SNARE and v‐SNARE) [, reviewed in ]. Aberrant α‐synuclein expression/conformation/localization may therefore impair neurotransmission in MPS IIIA brain .…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant α‐synuclein expression/conformation/localization may therefore impair neurotransmission in MPS IIIA brain . Nuclear localization indicates an additional role in the modulation of protein expression .…”
Section: Introductionmentioning
confidence: 99%